Human-hippo conflicts in Kenya during 1997-2008: Vulnerability of a megaherbivore to anthropogenic land use changes - Kanga, E.M.; Ogutu, Joseph O.; Piepho, Hans-Peter; Olff, H. (Informa UK Limited, 2012)
Rising human population and the associated demand for more land, water and other natural resources are intensifying conflicts between people and wildlife worldwide. We investigated the nature, intensity, seasonality, spatial and temporal patterns in human–hippo conflict incidences reported from wildlife stations Kenya-wide over a 12-year period spanning 1997–2008. Overall, 4493 human–hippo conflict incidences were recorded, representing a mean rate of 4.46 ± 0.29 incidences per month. The conflict incidences increased by 1285% from 1997 to 2008, resulting in 937 peak incidences reported in 2008. Number of conflict incidences differed among conservation regions, with incidences increasing during severe droughts and over time. Crop damage was the most commonly reported type of conflict. Wildlife managers attended to 90% of all reported conflict incidences. Hippo mortality increased linearly with increasing conflict incidences, portending a precarious future for hippos outside protected areas of Kenya. This dramatic rise in human–hippo conflicts is a consequence of fundamental land use changes around wetland habitats.